Antecedents of acquiring and developing green managerial competences - insights from the perspective of entrepreneurs and District Labour CEOs - Słupik, Sylwia; Trzęsiok , Joanna; Frączkiewicz-Wronka , Aldona; Łukasik , Damian; Morales-López , Nekane (Economics and Environment, 2025)
Purpose: Growing ecological, social, and regulatory pressures make acquiring green managerial competences essential for building competitive advantage. This study aimed to identify the antecedents of acquiring and developing green managerial competences from the perspectives of literature findings, District Labour CEOS, and entrepreneurs operating in the Silesia Region. Methodology: The study employed Principal Component Analysis (PCA) to analyse data from the survey (based on 71 structured questionnaires) conducted in May 2024 with District Labour Office CEOs and entrepreneurs in the Silesia Region. Findings: The findings contribute to the conceptualisation of green managerial competences, providing a basis for more precise definitions in future research. Respondents define these competences broadly, including green economy skills and personal, social, and interpersonal competences. Five key antecedents were identified: organisation, competition, self-development, socio-economic changes, and job loss, which significantly influence the achievement of organisations' competitive advantage, particularly in the context of the economy's transition towards sustainable development. Practical and social implications: Insights from the study guide managers in developing competences crucial for navigating the transition to a sustainable economy. Emphasising green competences promotes sustainable development and aligns organisational strategies with societal goals. Originality: This study addresses a research gap by enhancing the understanding of green managerial competences and identifying key factors influencing their development.